Analisis Sistem Pengendalian Piutang Pada PT ABC - Isqi, Riza Aulya; Vilantika, Elok (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The purpose of establishing a company is to develop, make a profit, ensure survival, and satisfy customers through its products and services. This research aims to understand and analyze the accounts receivable control system at PT ABC and to find appropriate solutions. The method used in this research is descriptive research with a qualitative approach. The results of the study indicate that the average accounts receivable turnover at PT ABC fluctuates and tends to increase, from 10.89 times in 2019 to 10.45 times in 2021, driven by increased sales. The accounts receivable collection period (ACP) also varies, from 34 days in 2019 to 35 days in 2020 and 2021. To minimize bad debts, the company can evaluate aspects such as character, capital, and collateral, and also consider external factors such as customer bankruptcy and internal factors from the provider of accounts receivable.